Solanum pimpinellifolium exhibits complex genetic resistance to Pseudomonas syringae pv. tomato - Hassan, Jana A.; Diplock, Nathan; Chau-Ly, Ilea J.; Calma, Jamie; Boville, Elizabeth; Yee, Steven; Harris, Taylor M.; Lewis, Jennifer D. (Frontiers in Plant Science, 2024)
Pseudomonas syringae pv. tomato (Pst) is the causal agent of bacterial speck disease in tomatoes. The Pto/Prf gene cluster from Solanum pimpinellifolium was introgressed into several modern tomato cultivars and provided protection against Pst race 0 strains for many decades.However, virulent Pst race 1 strains that evade Pto-mediated immunity now predominate in tomato-growing regions worldwide. Here we report the identification of resistance to a Pst race 1 strain (Pst19) in the wild tomato accession S. pimpinellifolium LA1589 (hereafter LA1589), using our rapid high-throughput seedling screen. LA1589 supports less bacterial growth than cultivars, and does not exhibit a hypersensitive response to Pst19. We tested an existing set of 87 Inbred Backcross Lines (IBLs) derived from a cross between susceptible Solanum esculentum E-6203 and Solanum pimpinellifolium LA1589 for resistance to Pst19. Using single-marker analysis, we identified three genomic regions associated with resistance. Bacterial growth assays on IBLs confirmed that these regions contribute to resistance in planta. We also mapped candidate genes associated with resistance in a cross between the Solanum lycopersicum var. lycopersicum cultivar Heinz BG-1706 and S. pimpinellifolium LA1589. By comparing candidates from the two mapping approaches, we were able to identify 3 QTL and 5 candidate genes in LA1589 for a role in resistance to Pst19. This work will assist in molecular marker assisted breeding to protect tomato from bacterial speck disease.